Kultur Resiko dan Taktik Pemuda Tani - Dien Vidia Rosa (DIMENSI - Jurnal Sosiologi, 2017)
Peasant today in neo-liberalism time is facing with land strengtening and agriculture labour sustainability. This article saw Sriharjo in agriculture area setting which is consider poor and observe significant transformation related to peasant values for their own land and opportunity shifting also labour problem. Young peasant in this context built narration of his susceptible, risk and position sustainability that saw state active role to encourage rural development in the sense of globalization and market openness which supply occupation opportunity in off-farm sector. Ethnography method is used as a frame to understand young peasant condition in struggling his ideas to sustain occupation scope especially due to cultural values changes of peasant society.